Time trends in cancer incidence in persons living with HIV/AIDS in the antiretroviral therapy era: 1997–2012. (17th July 2016) - Park, Lesley S.; Tate, Janet P.; Sigel, Keith; Rimland, David; Crothers, Kristina; Gibert, Cynthia; Rodriguez-Barradas, Maria C.; Goetz, Matthew Bidwell; Bedimo, Roger J.; Brown, Sheldon T.; Justice, Amy C.; Dubrow, Robert
Abstract : Objective: Utilizing the Veterans Aging Cohort Study, the largest HIV cohort in North America, we conducted one of the few comprehensive comparisons of cancer incidence time trends in HIV-infected (HIV+) versus uninfected persons during the antiretroviral therapy (ART) era. Design: Prospective cohort study. Methods: We followed 44 787 HIV+ and 96 852 demographically matched uninfected persons during 1997–2012. We calculated age-, sex-, and race/ethnicity-standardized incidence rates and incidence rate ratios (IRR, HIV+ versus uninfected) over four calendar periods with incidence rate and IRR period trend P values for cancer groupings and specific cancer types. Results: We observed 3714 incident cancer diagnoses in HIV+ and 5760 in uninfected persons. The HIV+ all-cancer crude incidence rate increased between 1997–2000 and 2009–2012 ( P trend = 0.0019). However, after standardization, we observed highly significant HIV+ incidence rate declines for all cancer (25% decline; P trend <0.0001), AIDS-defining cancers (55% decline; P trend <0.0001), nonAIDS-defining cancers (NADC; 15% decline; P trend = 0.0003), and nonvirus-related NADC (20% decline; P trend <0.0001); significant IRR declines for all cancer (from 2.0 to 1.6; P trend <0.0001), AIDS-defining cancers (from 19 to 5.5; P trend <0.0001), and nonvirus-related NADC (from 1.4 to 1.2; P trend = 0.049); and borderline significant IRR declines for NADC (from 1.6 to 1.4; P trend = 0.078) and virus-related NADC (from 4.9 to 3.5; P trend = 0.071). Conclusion: Improved HIV care resulting in improved immune function most likely contributed to the HIV+ incidence rate and the IRR declines. Further promotion of early and sustained ART, improved ART regimens, reduction of traditional cancer risk factor (e.g. smoking) prevalence, and evidence-based screening could contribute to future cancer incidence declines among HIV+ persons. Abstract : Supplemental Digital Content is available in the text